The effects of intra-articular tranexamic acid given intraoperatively and intravenous tranexamic acid given preoperatively on post surgical bleeding and transfusion rate post total knee arthroplasty (Medical Journal of Indonesia, 2016)
Background: Despite the advances in the design and fixation of implants in total knee replacement (TKR). the amount of postoperative bleeding is still an important issue that has not been resolved. This study aimed to measure the effectiveness of various tranexamic acid administration. Methods: This was a randomized controlled trial study, held from August 2014 to February 2016 at Cipto Mangunkusumo Hospital, Jakarta. Twenty two patients having TKR were divided into three groups: the control group, the tranexamic acid intra-articular-intraoperative group, and the intravenous preoperative group. Intraoperative bleeding, haemoglobin (Hb) level on preoperative to five-day-post-surgery, total drain production, total blood tranfusion needed and the drain removal timing were recorded and compared. Numerical data were analyzed by using parametric and non-parametric test, depended on the normality of the data. Results: The amount of blood transfusion needed in both the intra-articular group (200±SD 100 mL) and the intravenous group (238±SD 53 mL) were significantly different compared to those in the control group (1,016±SD 308.2 mL) (p=0.001). Meanwhile, there was no significant difference between the amount of blood transfusion needed in the intra-articular group and the intravenous group. Total drain production in the intra-articular group (328±SD 193 mL) and intravenous group (391±SD 185 mL) was significantly different compared to the control group (652±SD 150 mL) (p=0.003). No significant difference between the levels of both preoperative and postoperative haemoglobin, the amount of intraoperative bleeding, and the duration of drain usage. Conclusion: Intravenous and intra-articular tranexamic acid effectively decreased transfusion volume and drain production in patients undergoing TKR.